Avaliação físico-química e sensorial do grão de café arábica submetido à secagem solar, convectiva e por cast-tape drying - Coelho, Emerson Gonçalves (2022)
The coffee fruit is preferably harvested at the cherry stage, with high water content and greater metabolic activity, and then it must be subjected to a process of removing moisture for better conservation of the grain and its flavor. In this context, the objective of this study was to characterize the final quality of arabica coffee of the Arara cultivar, processed by wet process and submitted to six drying methods: three carried out in the agro-industrial establishment (fixed bed dryer, rotary drum dryer and combined drying) and three laboratory scale methods (convective oven, cast-tape drying and suspended terrace). The fruits of demucilated in natura coffees and the processed dried coffee beans were characterized in terms of moisture, ash content, nitrogen compounds, lipids, total titratable acidity, organic acids, sugars, instrumental color of the beans and sensory analysis. The averages of the analyzes were calculated and submitted to ANOVA with a 5% level of significance in the test. Drying on the suspended terrace, which lasted 6 days, required the longest operating time so that the moisture (b.u.) of the coffee was reduced from an initial value of 46.2% to an average value of 11.35%. The contents of ash, lipids and total titratable acidity found in the dry coffee samples are in accordance with the literature and without significant differences between the drying treatments analyzed. Contents of nitrogen compounds obtained for the coffee samples showed significant differences (with 95% confidence) and the highest values were found in the convective oven, Cast-tape dryer and fixed bed dryer processes. Citric, malic and succinic acids were found in the samples, and the concentrations of citric and malic acids did not show significant differences between the drying treatments. . In none of the evaluated samples were found acetic acid, butyric acid, lactic acid and propionic acid. The fructose and glucose contents found in the coffee beans had a decrease after drying, while the sucrose content increased. The results for the a* color coordinate with negative values showed a greenish coloration of the coffee beans. The sensory profile of arabica coffee was evaluated by five coffee experts using the methodology proposed by the Specialty Coffee Association (SCA) obtaining values between 83.45 and 86.75 on the SCA scale (no significant differences) and who classified all coffees as special. The drying methods in the parameters used were adequate, and drying in the suspended terrace was the method whose main advantage is not to use electrical energy during the process and drying in the fixed bed dryer is what requires less movement of the coffee until the beginning of the drying process.